Musical Semiotics – a Discipline, its History and Theories, Past and Present - Tarasti, Eero (Recherches sémiotiques / Semiotic Inquiry, 2016)
Musical semiotics begins from the premise that music is a signifying phenomenon. However, the field itself has developed according to two distinct paths. The first one starts by considering music and its history. In the study of classical music, for instance, it will begin by considering rhetoric and affect during the Baroque period and then move to consider the topics of the Classical style or the interartistic aspects of Romanticism. The other path consists instead of applying general semiotic theories to music. A more proper approach, I believe, lies somewhere in the middle : it ought to configure general semiotic concepts to the special or historical problems of music. In this essay I give examples from my own work borrowing methodology from the Paris School of Semiotics developed by Greimas and from my own Existential Semiotics model.